Parkinson’s Disease and Depression: An Update Clinical Perspective - Arinafril, Nabila Khairunisah (HM Publisher, 2023)
Parkinson's disease is a progressive neurodegenerative disease and its prevalence continues to rise. The correlation between depression and the quality of life of Parkinson's patients has been proven by several studies that depression can affect up to 40-50% of the aspects assessed in the Parkinson's disease questionnaire (PDQ-39) questionnaire and also significantly affects the decline in quality of life of Parkinson's patients. Therefore, a multidisciplinary approach, apart from medication and therapy in the management of this disease, is very important to improve the overall outcome and quality of life related to Parkinson patients’ health.